Pengaruh Struktur Modal Terhadap Profitabilitas pada Perusahaan Financial Technology Peer To Peer Lending yang Terdaftar di OJK pada Tahun 2019-2023 - Sofiatul Laeliyah; Suherman; Titis Fatarina Mahfirah (Teewan Journal Solutions, 2025)
This study aims to determine the effect of capital structure on the profitability of peer-to-peer lending financial technology companies in Indonesia. The population of this study was peer-to-peer lending fintech companies registered with the Financial Services Authority (OJK) between 2019 and 2023. The independent variable is capital structure, calculated using the debt-to-asset ratio (DAR), debt-to-equity ratio (DER), and long-term debt-to-equity ratio (LDER). The dependent variable is profitability, calculated using return on assets (ROA), return on equity (ROE), and net profit margin (NPM). This study uses firm size, firm growth, and current ratio as control variables. The sample used in this study was 56 companies with a total of 196 observations. This study used unbalanced panel data. The research method used panel data regression analysis using STATA 17 software. The results show that capital structure, using DAR, DER, and LDER as proxies, has a negative effect on profitability, measured by ROA, ROE, and NPM.